2021
DOI: 10.1038/s41562-021-01129-1
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic normalization model of temporal attention

Abstract: Vision is dynamic, handling a continuously changing stream of input, yet most models of visual attention are static. Here, we develop a dynamic normalization model of visual temporal attention and constrain it with new psychophysical human data. We manipulated temporal attention–the prioritization of visual information at specific points in time–to a sequence of two stimuli separated by a variable time interval. Voluntary temporal attention improved perceptual sensitivity only over a specific interval range. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(99 citation statements)
references
References 105 publications
7
81
1
Order By: Relevance
“…At first glance, the beneficial consequence that temporal expectation in one task has on performance in another task may seem to contradict findings related to the selective nature of temporal expectations. For example, previous research has demonstrated that directing attention to a target occurring at one point in time leads to performance benefits at that specific time but simultaneously to impairments earlier and later (Denison et al, 2017(Denison et al, , 2021. Instead, we show that temporal expectations can facilitate performance of the task to which they are applied, as well as the preceding intervening task.…”
Section: A Between-task Consequence Of Temporal Expectationscontrasting
confidence: 73%
“…At first glance, the beneficial consequence that temporal expectation in one task has on performance in another task may seem to contradict findings related to the selective nature of temporal expectations. For example, previous research has demonstrated that directing attention to a target occurring at one point in time leads to performance benefits at that specific time but simultaneously to impairments earlier and later (Denison et al, 2017(Denison et al, , 2021. Instead, we show that temporal expectations can facilitate performance of the task to which they are applied, as well as the preceding intervening task.…”
Section: A Between-task Consequence Of Temporal Expectationscontrasting
confidence: 73%
“…Moreover, it can shed new light on a fundamental question of attention research, namely whether attention is space-based or object-based (e.g., 63-66; for a review, see 67). Finally, accurate estimation of the size and shape of the attention focus, as well as its temporal and spatial dynamics during voluntary (endogenous) or automatic (exogenous) attentional orienting, or prior to goal-directed actions has crucial implications for conceptual and computational models of visual attention (e.g., 7,50,68-70).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the authors estimated that it took ~1 s for attentional gain to recover. Because all behaviour is constrained in time, the formalisation and estimation of dynamic voluntary attention may have broad relevance beyond the specific task employed in [1]. In the following we therefore first reflect on the findings in light of the unique task properties, before outlining promising future directions opened by this landmark demonstration.…”
Section: Modelling and Quantifying Voluntary Selective Attention Acro...mentioning
confidence: 99%
“…First, the participants in [1] were required to temporarily store two stimuli in memory Box 1. What is the 'time' in temporal attention?…”
Section: Temporal Task Properties and Their Theoretical Relevancementioning
confidence: 99%
See 1 more Smart Citation